GE_GERICHTE C/5481/2011 vom 21. September 2012 - GE Cour de justice (2012)
CONTRAT D'ENTREPRISE; VICE DE CONSTRUCTION; DOMMAGE; PRESCRIPTION; RENONCIATION(SENS GÉNÉRAL); DEVOIR PROFESSIONNEL; PREUVE ILLICITE | CO.135 CO.371a CPC.152.2 LLCA.12